2021
DOI: 10.3390/microorganisms9040720
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a New Resistance-Mediating Plasmid Chimera in a blaOXA-48-Positive Klebsiella pneumoniae Strain at a German University Hospital

Abstract: Mobile genetic elements, such as plasmids, facilitate the spread of antibiotic resistance genes in Enterobacterales. In line with this, we investigated the plasmid-resistome of seven blaOXA-48 gene-carrying Klebsiella pneumoniae isolates, which were isolated between 2013 and 2014 at the University Medical Center in Göttingen, Germany. All isolates were subjected to complete genome sequencing including the reconstruction of entire plasmid sequences. In addition, phenotypic resistance testing was conducted. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…For the German isolate, neither the collection date nor the origin location was available. However, the German sequence has been previously described in several publications [ 84 , 98 , 99 ]. In a recent report on a K. pneumoniae ST23 outbreak in Göttingen, Germany, in 2013, it was shown, that at least one outbreak isolate seemingly carried an identical plasmid [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the German isolate, neither the collection date nor the origin location was available. However, the German sequence has been previously described in several publications [ 84 , 98 , 99 ]. In a recent report on a K. pneumoniae ST23 outbreak in Göttingen, Germany, in 2013, it was shown, that at least one outbreak isolate seemingly carried an identical plasmid [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the German sequence has been previously described in several publications [ 84 , 98 , 99 ]. In a recent report on a K. pneumoniae ST23 outbreak in Göttingen, Germany, in 2013, it was shown, that at least one outbreak isolate seemingly carried an identical plasmid [ 98 ]. Note that the occurrence of many carbapenemase-negative genomes in multiple countries likely indicates that production of these enzymes is not the only driver of successful dissemination of ST395, however.…”
Section: Discussionmentioning
confidence: 99%
“…All the S. fonticola strains also harboured numerous fluoroquinolone resistance genes, raising a health concern for treatment options, as fluoroquinolones are often used for management of conditions including typhoid fever and MDR tuberculosis (Richards et al, 2019). Interestingly, one S. fonticola strain harboured an acquired trimethoprim (sul2) resistance gene associated with IS110, corresponding to K. pneumoniae from a German university hospital (Schwanbeck et al, 2021). The Serratia genus naturally lacks resistance genes for trimethoprim and sulfonamides (Sandner-Miranda et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…The research paper by Bilal et al [ 5 ] reported the occurrence of bla NDM-1 bearing IncX3 plasmid in clinically isolated ST11 Klebsiella pneumoniae from Pakistan. A new resistance-mediating plasmid chimera was detected in bla OXA-48 -positive Klebsiella pneumoniae strain at a German university hospital [ 6 ]. HI2 plasmids mobilising the carbapenemase gene bla IMP-4 were identified both in Escherichia coli Australian clinical samples and in multiple sublineages of E. coli ST216 colonising silver gulls [ 7 ].…”
mentioning
confidence: 99%